The Efficacy of Oral Magnesium in Reducing Headache Frequency and Intensity - منهل نبيل يوسف (Latakia University Journal -Medical Sciences Series, 2022)
Primary headache is a common neurological disorder adversely affecting quality of life and productivity, underscoring the need for safe and effective preventive treatments. This randomized, single-blind, placebo-controlled clinical trial evaluated the efficacy of oral magnesium supplements at doses of 200, 400, and 600 mg in reducing headache frequency, intensity, and duration among 32 patients. The intervention lasted eight weeks following a two-week baseline period, during which analgesic use was prohibited. Results demonstrated a statistically significant reduction (~50%) in headache frequency in the 400 mg and 600 mg groups after four weeks, accompanied by notable improvements in pain severity and duration, with sustained effects through the study period. The 600 mg dose was associated with a slight increase in gastrointestinal side effects, while the 400 mg dose offered a more optimal balance of efficacy and tolerability. These findings suggest that daily oral magnesium supplementation at 400 mg is a safe and effective preventive option for primary headache, warranting further larger and longer-term studies to confirm these results.